2021
DOI: 10.3390/su13179842
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Detailed Standards to Control Non-Point Source Pollution Priority Management Areas: Centered on Highland Agriculture Watershed

Abstract: The Ministry of Environment in Korea aims to reduce non-point source (NPS) pollution and improve soil water management by expanding NPS priority management areas. Six NPS priority management areas to reduce suspended solids (SS) according to soil loss were chosen as they either constitute serious hazards to the natural ecosystem due to NPS pollutants or they are areas with unusual geologic structure or strata. Although more comprehensive standards are required for effective NPS management, however, no detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Almost all of the pollution originates from agricultural NPSP and domestic sewage. At present, the research on NPSP in this area is mainly focused on NPSP output characteristics, pollution load estimation, pollution prevention and control technologies and management Kim et al, 2021). However, the study of the effect of NPSP on microbial ecological processes in river sediments has not been reported in detail, especially the mechanism underlying the effect of NPSP on fungal community construction in sediments, which is still unclear .…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the pollution originates from agricultural NPSP and domestic sewage. At present, the research on NPSP in this area is mainly focused on NPSP output characteristics, pollution load estimation, pollution prevention and control technologies and management Kim et al, 2021). However, the study of the effect of NPSP on microbial ecological processes in river sediments has not been reported in detail, especially the mechanism underlying the effect of NPSP on fungal community construction in sediments, which is still unclear .…”
Section: Introductionmentioning
confidence: 99%
“…According to data, NPS contamination has harmed 30-50% of surface water sources, making it an increasingly serious threat to water quality and aquatic ecosystem restoration [3]. Every year, approximately 0.3-0.8% of cropland worldwide is impacted by severe deterioration, rendering the soil unsuitable for agricultural production [4,5]. Concerning this, NPS pollution has emerged as the primary contributor to water pollution in many Korean rivers and lakes, leading to the degradation of water quality [6].…”
Section: Introductionmentioning
confidence: 99%
“…Kabir et al (2021) indicated that tire wear from vehicles on roads might release synthetic rubber particles into rivers. Thus, rubber from tires, etc., circulates in the ecosystem as a non-point pollution source (NPS) due to various causes, such as rainfall (Kim et al, 2021). MPs in NPS can ow into various water sources and increase the concentrations of MPs, and many studies have reported that MPs are ingested throughout the food-chain (Cole et al, 2011).…”
Section: Introductionmentioning
confidence: 99%